An extended simultaneous algebraic reconstruction technique (E‐SART) for X‐ray dual spectral computed tomography. Issue 6 (9th February 2016) - Hu, Jingjing; Zhao, Xing; Wang, Feng
Summary: X‐ray dual spectral computed tomography (DSCT) scans the measured object with two different x‐ray energy spectra and the collected polychromatic projections from this procedure can be used to perform basis material decomposition of the object. An iterative method E‐ART was recently proposed to produce highly quantitative basis material images for DSCT, but it has the drawback of slow convergence and huge computational costs. Inspired by the E‐ART method, this paper proposes an extended simultaneous algebraic reconstruction technique (E‐SART) for the basis material decomposition of DSCT and an accelerating strategy for improve the convergence speed of the iterative reconstruction. Compared with the E‐ART method, the proposed method has much faster convergence rate while at the same time it has better noise suppressing feature. The advantages of this method were verified by experiments in which the FORBILD thorax phantom was iteratively reconstructed from noise‐free and noisy polychromatic projections. SCANNING 38:599–611, 2016. © 2016 Wiley Periodicals, Inc.